2012
DOI: 10.1007/s12144-012-9131-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Identity Style and Parental Identification to Predict Political Orientation

Abstract: There has been a recent increase in interest in the psychological differences and antecedents related to political orientation. Personality, disgust sensitivity, attachment, and closeness to parents have all been found or have been theorized to be predictive of political orientation. These variables and the additional roles played by normative identity style and parental identification were examined. The results showed that normative identity style is associated with political orientation and that the role pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Primes were unrelated to liberalism/conservativism and are not discussed further. Dunkel and Decker (2012) found that ambivalent and avoidant attachments were related to liberalism, and Thornhill and Fincher (2007) observed that secure attachments were associated with an indicator of conservatism, C-Scale scores. In contrast, Weise et al (2008) reported that security of attachment was associated with liberal ideology.…”
Section: Independent Variable: Attachment Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Primes were unrelated to liberalism/conservativism and are not discussed further. Dunkel and Decker (2012) found that ambivalent and avoidant attachments were related to liberalism, and Thornhill and Fincher (2007) observed that secure attachments were associated with an indicator of conservatism, C-Scale scores. In contrast, Weise et al (2008) reported that security of attachment was associated with liberal ideology.…”
Section: Independent Variable: Attachment Theorymentioning
confidence: 99%
“…Research on adult attachment and ideology. Studies of adult attachment as a psychological aspect of political ideology in college students, either in experiments or surveys in the United States, yield conflicting results (Dunkel & Decker, 2012;Gillath & Hart, 2010;Koleva & Rip, 2009;Thornhill & Fincher, 2007;Weber & Federico, 2007;Weise et al, 2008). Student samples diverge enough from nonstudent samples in political interest and knowledge and other characteristics that general population samples should be preferred when studying such constructs (Koleva & Rip, 2009).…”
Section: Independent Variable: Attachment Theorymentioning
confidence: 99%
See 3 more Smart Citations